Kepuasan Nasabah Sebagai Variabel Intervening Pada Pengaruh Customer Relationship Management Terhadap Loyalitas Nasabah - Indah Yuliyanti; Fani Firmansyah (Jurnal Ecogen, 2023)
This research was conducted at one of the Islamic banks in the city of Blitar, namely PT Bank Syariah Indonesia Blitar branch. This study objectives to determine the effect of customer relationship management on loyalty through customer satisfaction at the Blitar branch of Indonesian Islamic banks. This research is  quantitative research with a descriptive approach. The population in this study were all customers of the Blitar branch of the Indonesian Islamic bank. The sampling technique uses non-probability sampling through purposive sampling by determining several considerations that have been determined by the researcher. This study used primary data by distributing questionnaires to 100 customers of the Blitar branch of the Indonesian Islamic bank. The data analysis method used is calculation using the Partial Least Square (PLS) method with the help of the SmartPLS version 3 software program and the Sobel test. The results showed that customer relationship management has a significant effect on customer loyalty. Customer relationship management affects customer satisfaction. Customer satisfaction affects customer loyalty. Customer satisfaction mediates customer relationship management on customer loyalty. This research is expected to be a source of information and referrals for companies as a strategy to create customer loyalty